The Significance of the Association of Letters of Meanings with Each Other in the Quranic Context (Hamza and what is associated with as a model) - Bahloul Al-Jubouri, Nafeh Alwan; Muhammad, Yas Khader (Journal of Tikrit University for Humanities, 2021)
This research aims to reveal the functional performance of the hamza through its association with the letters of meanings in the Qur’an context. In this case, the meaning of the hamza is restricted to other letters associated with it, and changing these letters leads to a change of meaning, so the meaning that is intended from the association of (the hamza) with (the Baa) is not the meaning of its conjunction with (Faa) or (Waw al-Hal), and so on with the rest of the letters . The present study is consisted of an introduction and two sections, followed by the conclusion with a summary of the results obtained from the research.